Why Is Veteran Unemployment So High? - Loughran, David S. (RAND Corporation, 2014)
Between 2000 and 2011, younger veterans were more likely to be unemployed than younger non-veterans. This difference falls rapidly with age and time. The evidence supports the hypothesis that veteran unemployment reflects engagement in job search. There is little evidence that veterans are disadvantaged in the labor market. Limiting benefits to veterans might reduce the length of unemployment spells, but the budgetary effect is unclear.